2021
DOI: 10.1136/ebmental-2021-300318
|View full text |Cite
|
Sign up to set email alerts
|

Methods and efficacy of social support interventions in preventing suicide: a systematic review and meta-analysis

Abstract: QuestionSuicide is a global public and mental health problem. The effectiveness of social support interventions has not been widely demonstrated in the prevention of suicide. We aimed to describe the methods of social support interventions in preventing suicide and examine the efficacy of them.Study selection and analysisWe searched literature databases and conducted clinical trials. The inclusion criteria for the summary of intervention methods were as follows: (1) studies aimed at preventing suicide through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…After examining randomized controlled trials utilizing social support as treatment, they found a non‐significant result of lowered suicide attempts in the intervention group compared to treatment as usual, while death by suicide was reduced by 53% (Hou et al, 2022). The methods employed by these RCTs included one‐to‐one intervention using postcards, text messaging, face‐to‐face, telephone, or email contact by laypersons or professionals, while group interventions included group meetings or integrated group activities such as hiking or volunteering (Hou et al, 2022). These mixed findings may be due to interventions utilizing professionals or strangers rather than bolstering the existing relationships one has, specifically their family relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After examining randomized controlled trials utilizing social support as treatment, they found a non‐significant result of lowered suicide attempts in the intervention group compared to treatment as usual, while death by suicide was reduced by 53% (Hou et al, 2022). The methods employed by these RCTs included one‐to‐one intervention using postcards, text messaging, face‐to‐face, telephone, or email contact by laypersons or professionals, while group interventions included group meetings or integrated group activities such as hiking or volunteering (Hou et al, 2022). These mixed findings may be due to interventions utilizing professionals or strangers rather than bolstering the existing relationships one has, specifically their family relationships.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are important to understand the aetiology of suicidality and should be reinforced as specific targets for treatment when dealing with depressed patients at risk of suicidal behaviour. A recent meta-analysis by Hou et al (2022) highlights the inconsistencies in the treatment of suicidality using social support methods. After examining randomized controlled trials utilizing social support as treatment, they found a non-significant result of lowered suicide attempts in the intervention group compared to treatment as usual, while death by suicide was reduced by 53% (Hou et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, our results show that psychosocial factors such as stressful experiences and social relationships are particularly important in screening for elevated suicide risk in males. Moreover, targeted social interventions such as offering social skills training and social support, providing opportunities for positive social engagement, and challenging maladaptive social cognition ( 53 ) may prove beneficial for suicide prevention efforts ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…SAs are preventable behaviours that usually emerge when individuals think of death as the only option to escape unbearable suffering (Pompili et al, 2008). Although several public health interventions can be put in place to prevent suicide at the population level (Hofstra et al, 2020; Hou et al, 2022; Mann et al, 2021), and psychotherapeutic (Brown et al, 2005; Büscher et al, 2020; Stanley & Brown, 2012) or pharmacological approaches (Baldessarini et al, 2006a; Zalsman et al, 2016) can be successfully implemented at the individual level, clinical tools to predict who is more likely to attempt suicide are somewhat limited, and mainly subject-dependent (Haney et al, 2012). In this context, neuroimaging markers bear the essential properties of representing fruitful objective measures of one’s risk of death by suicide (Sudol & Mann, 2017).…”
Section: Discussionmentioning
confidence: 99%